Co-pyrolysis of waste polyvinyl chloride and oil-based drilling cuttings: Pyrolysis process and product characteristics analysis. (10th October 2021) - Xia, Zebang; Yang, Hang; Sun, Jianfa; Zhou, Zejun; Wang, Jing; Zhang, Yi
Abstract: Oil-based drill cuttings (OBDC) and waste polyvinyl chloride (waste PVC) both are solid wastes. The pyrolysis/co-pyrolysis characterizations of OBDC, waste PVC and OBDC/waste PVC at varying heating rates were investigated using thermogravimetric analysis (TG/TGA). Coats-Redfern and Kissinger integration methods were employed to fit the TG curve. The optimal fitting effect was obtained with reaction order at 2 and Kissinger integration method was better than Coats-Redfern integration method for co-pyrolysis of OBDC/waste PVC. The practical co-pyrolysis condition was optimized using batch experiment and the optimal condition was as following: final temperature for 600 °C, holding time for 60 min, heating rate at 10 °C/min and ratio of PVC as 10% PO. The gas, solid and liquid phase products of pyrolysis/co-pyrolysis were characterized and analyzed using thermogravimetry-mass spectrometry (TG-MS), gas chromatography-mass spectrometry (GC-MS) and X-ray diffraction (XRD). The gas product of pyrolysis/co-pyrolysis indicated the inhibitory effect on HCl emission due to the positive synergic effect of OBDC and PVC. High pyrolysis temperature was beneficial to increase the content of hydrocarbons, which enhanced the quality of oil recovery. This study indicated that the co-pyrolysis of OBDC and waste PVC is a promising method for waste disposal and oil recovery. Highlights: The co-pyrolysis of the OBDC and PVC were carried out at first. Coats-Redfern integration and Kissinger integration methods was compared. HCl emission was reduced due to the positive synergic effect of OBDC and PVC. The co-pyrolysis could reduce the formation of SO2 gas in the OBDC.